Penerapan Restorative Justice dalam Penanganan Anak sebagai Pelaku Tindak Pidana dalam Perspektif Hukum Islam - Miftahhurahmah Miftahhurahmah; Miswardi Miswardi; M. Khairul Arwani; Zulheldi Zulheldi (Journal of Islamic Law and Wisdom, 2025)
Handling of children as perpetrators of criminal acts cannot be equated with adults. This study aims to examine the application of restorative justice in handling children as perpetrators of criminal acts and the perspective of national criminal law and Islamic criminal law. The type of research conducted is library research with data sourced from primary, secondary and tertiary data sources. The collected data is then analyzed using qualitative data analysis methods. This study concludes that the application of restorative justice in resolving criminal acts whose perpetrators are in the criminal law system in Indonesia is relatively new since the birth of the Child SPPA Law which regulates the diversion mechanism in it. According to this regulation, children who commit crimes with a threat of less than 7 (seven) years must be resolved using a diversion mechanism. The restorative justice approach is indeed not known in Islamic criminal law, but its principles are identical to the practice of diyat and peace (ishlah) in Islamic criminal law.